2020
DOI: 10.1021/jacs.0c06582
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Giant Mo240 Hollow Opening Dodecahedra

Abstract: The synthesis of hollow opening polyhedral cages has always been an attractive but challenging goal, especially with regard to inorganic polyhedral cages. Herein, we present a novel, 240-nuclearity giant polymolybdate cage prepared via hydrothermal synthesis. This cage is composed of 20 tripod-shaped [Mo6O22(SO3)] n−/[Mo6O21(SO4)] n− building blocks with three connected vertices and 30 cubane-type [Mo4O16] n− edge building blocks, featuring a rare, nearly regular pentagonal dodecahedron with a large inner cavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
123
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(131 citation statements)
references
References 50 publications
5
123
1
2
Order By: Relevance
“…Each [Mo 4 O 16 ] 8− anion was observed to be composed of four edge-sharing Mo VI O 6 octahedra units (Fig. 2b), similar to the reported cubane-like structures with T d point group symmetry, 40,41 and having Mo-O bond distances ranging from 1.705(10) to 2.288(19) Å. We also performed bond valence sum (BVS) calculations (Table S3, ESI †), which demonstrated a + 6 valence for the Mo ions.…”
supporting
confidence: 85%
“…Each [Mo 4 O 16 ] 8− anion was observed to be composed of four edge-sharing Mo VI O 6 octahedra units (Fig. 2b), similar to the reported cubane-like structures with T d point group symmetry, 40,41 and having Mo-O bond distances ranging from 1.705(10) to 2.288(19) Å. We also performed bond valence sum (BVS) calculations (Table S3, ESI †), which demonstrated a + 6 valence for the Mo ions.…”
supporting
confidence: 85%
“…[40] In the high-resolution XPS of Mo 3d (Figure 4b), two peaks at 232.69 and 235.85 eV with a splitting width of 3.2 eV for Compound 1 as synthesized can be deconvoluted, which is consistent with those reported in literature for Mo 6 + . [41] Despite displacement of 0.4 eV of XPS, Mo(V) can be hardly generated through reduction process of Mo(VI) to Mo(V) at the high potentials required for water oxidation, this peak of 232.24 eV should be considered as Mo(VI)-3d 5/2 .…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…The excellent proton conductivity should be attributed to the presence of rich proton carriers within the structure of 1Ln, including water molecules, terminal oxygen atoms, and organic amines, which help to form hydrogen-bonded proton "hopping" networks. 38,39 The relatively low humidity-dependent characteristic and high proton conductivity make us further explore the conducting performance of 1Ln at subzero temperature. Given that the proton-conducting properties of 1Sm are slightly superior to 1Eu, 1Sm was chosen as representative for subzero conducting test in the temperature range of -40°C -0 o C. Interestingly, 1Sm shows a high proton conductivity of 1.78 × 10 −5 S cm -1 even at -40°C (Figure 3c), which is much better than known crystalline POM proton conductor at -40°C.…”
Section: Introductionmentioning
confidence: 99%
“…11 The E a of 1Sm and 1Eu were calculated by Arrhenius equation σT = σ 0 exp(E a /k b T) to be 0.30 eV and 0.32 eV (Figure 3d and Supporting Information Figure S4), respectively, suggesting that their proton transfer processes follow the Grotthus mechanism, typically the E a below 0.4 eV. [37][38][39] Compared with the E a (0.3 eV) above RT, the E a of 1Sm under subzero temperature increases to 0.38 eV, still belonging to Grotthus mechanism (Figure 3d and Supporting Information Figure S5). PXRD after testing confirmed that structures of 1Ln maintain intact throughout the whole measurement process (Supporting Information Figure S6).…”
Section: Introductionmentioning
confidence: 99%